Art workshops for children - Tullet, Hervé, ....- (London : Phaidon, 2015)
A guide to twelve children's art workshops by one of the world's most innovative facilitators and best–selling bookmakers. Art Workshops for Children is a guide for parents and teachers to organize and execute artistic workshops for children. 12 workshops are featured, each offering a list of materials needed, a step–by–step guide to facilitation, practical tips, illustrated examples, and photos of workshops in progress. The workshops are designed to spark children's imaginations, champion group bonding, and give visually pleasing results – with no artistic ability required. Tried and tested around the world by children of all ages. Perfect for organizing group events at home, in schools, at parties, at museums – anywhere!
Keywords: Kunst ; kinderen